RELATIONSHIP BETWEEN NUTRIENT INTAKE AND PREMENSTRUAL SYNDROME IN STUDENTS OF MUHAMMADIYAH MADIUN MIDWIFERY ACADEMY - Hayun Manudyaning susilo (Universitas Muhammadiyah Ponorogo, 2021)
Premenstrual Syndrome in adolescents is still a health problem in Indonesia.Shortly before menstruation, commonly referred to as premenstrual syndrome (PMS). One of the causes of PMS is a lack of nutrient intake. To reduce the occurrence of premenstrual syndrome is exercise, reduce caffeine, nicotine, alcohol, sugar, salt, rest enough, pay attention to nutrition and nutrition. In this case nutrient intake in adolescents is something important and is expected to be able to deal with this problem of premenstrual syndrome. The research design uses Cross Sectional. The population in this study was 156 students who attended Muhammadiyah Madiun Midwifery. The samples in this study were some of the students of Muhammadiyah Madiun Midwifery academy which amounted to 112, taken by Purposive sampling.The research instruments used are food recall and questionnaire , the results were analyzed using Spearman Rank test with signification level α=0.05. The results found that almost all of them were 104 people (92.9%) have moderate Premenstrual Syndrome. While respondents who have moderate nutritional status is as many as 53 people (47.3%). Spearman Rank test got a result of ρ=0.002. Based on the results of the above research can be concluded that there is a relationship between nutritional status and the incidence of Premenstrual Syndrome in young women. Therefore, it is recommended in young women to maintain a good nutritional intake, so as to prevent Premenstrual Syndrome